The Wooden Horse - Walpole, Hugh, 1884-1941 (Salt Lake City, UT : Project Gutenberg, 2008)
"The Wooden Horse" by Hugh Walpole is a novel written in the early 20th century. The story unfolds around Robin Trojan, a young man steeped in the traditions of his prominent family, as he awaits a long-anticipated reunion with his estranged father, Henry Trojan, whom he has not seen for eighteen years. The narrative explores themes of familial duty, social status, and the complexities of adapting to change, as Robin navigates the expectations of his lineage and the intriguing dynamics of reuniting with a father whose life has diverged drastically from his own. At the start of the book, the atmosphere is charged with anticipation as Robin prepares to meet his father. The scene is set in the grand but uncomfortable drawing room of their family home, highlighting the rigidity of the Trojan legacy. Robin's anxiety about his appearance and the family's expectations reflects his internal struggle with identity, particularly as they are juxtaposed with Henry's more relaxed demeanor, influenced by his years in New Zealand. As the characters gather for this momentous event, Robin's seemingly superficial concerns about appearances clash with deeper tensions related to family pride and the acceptance of change. The opening effectively establishes the familial dynamics and lays the groundwork for the emotional and social exploration that will follow. (This is an automatically generated summary.)
Release date is 2008-11-06
Produced by Al Haines
Keywords: Fathers and sons -- Fiction; Cornwall (England : County) -- Fiction